PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA MELALUI MOTIVASI KERJA PADA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN LOMBOK BARAT - Wardani, Rosyia (Sekolah Tinggi Ilmu Ekonomi AMM Mataram, 2017)
The purpose of this study were (1) To determine the significance of the effect of financial compensation to the Employee work motivation. (2) To determine the significance of the effect of non-financial compensation for work motivation. (3) To determine the significance of financial compensation effect on job satisfaction. (4) To determine the significance of non-financial compensation effect on job satisfaction. (5) To determine the significance of the effect of work motivation on job satisfaction.This type of research used in this research is associative or causal (causal). Data collection method used in this research is census method on 128 Employee Dikpora East Lombok. Data collection tool using a questionnaire and analyzed using path analysis (path Analysis) with the help of the program Amos 21 for windows.The results showed (1) Compensation Financial has a positive and significant effect on work motivation. (2) Compensation Nonfinancial has a positive and significant effect on work motivation. (3) Financial compensation has a positive but not significant effect on job satisfaction. Financial compensation has a significant impact on job satisfaction when through work motivation (4) Compensation Nonfinancial have a positive but not significant effect on job satisfaction. Compensation Nonfinancial have a significant impact on job satisfaction through work motivation. (5) Work motivation has a positive and significant impact on job satisfaction